Surface seeding-cum-mulching technique An emerging option to manage crop residue - Kumar, Anil; Singh, Gurbachan (Indian Farming, 2024)
Surface seeding cum mulching of wheat is an emerging low-cost eco-friendly technique of managing paddy straw, where paddy harvesting and wheat sowing are done simultaneously. Compared to existing residue managemental options, this method has benefits with respect to weed control, soil health as well as crop productivity along with economic benefits as costly machines and high-power tractors are not required in this technique. Straw management and sowing operation of wheat can be completed with a meagre cost of ₹ 650-700 only compared to ₹ 2000-2500 per acre for conventional methods. This technique provides complete mulching, which keeps the soil profile moist and saves the crop from terminal heat stress. Moreover, crop resist to lodging as well as withstand against adverse conditions like torrential rain and hailstorms. Besides, this technique reduces dependence on costly herbicide inputs as it ensures mostly weed free crop.